The American Revolution and the Habsburg Monarchy. By Jonathan Singerton (Charlottesville: University of Virginia Press, 2022), 352pp. - Martin Gabriel (Journal of the Austrian Association for American Studies, 2022)
Martin Gabriel reviews Jonathan Singerton's monograph The American Revolution and the Habsburg Monarchy (2022).